TwinF interface inhibitor FP802 stops loss of motor neurons and mitigates disease progression in a mouse model of ALS - Yan, Jing; Wang, Yumeng; Hellwig, Andrea; Bading, Hilmar (Cell reports. Medicine, 2024)
Toxic signaling by extrasynaptic NMDA receptors (eNMDARs) is considered an important promoter of amyotrophic lateral sclerosis (ALS) disease progression. To exploit this therapeutically, we take advantage of TwinF interface (TI) inhibition, a pharmacological principle that, contrary to classical NMDAR pharmacology, allows selective elimination of eNMDAR-mediated toxicity via disruption of the NMDAR/TRPM4 death signaling complex while sparing the vital physiological functions of synaptic NMDARs. Post-disease onset treatment of the SOD1G93A ALS mouse model with FP802, a modified TI inhibitor with a safe pharmacology profile, stops the progressive loss of motor neurons in the spinal cord, resulting in a reduction in the serum biomarker neurofilament light chain, improved motor performance, and an extension of life expectancy. FP802 also effectively blocks NMDA-induced death of neurons in ALS patient-derived forebrain organoids. These results establish eNMDAR toxicity as a key player in ALS pathogenesis. TI inhibitors may provide an effective treatment option for ALS patients.
Online verfügbar 6. Februar 2024, Artikelversion 20. Februay 2024
Gesehen am 28.03.2024